The Saint-Venant Torsion of a Cartesian Orthotropic Bar With an Isosceles Right-Angled Triangle Cross-Section - ECSEDI, István; BAKSA, Attila (Engineering Transactions, 2024)
The Saint-Venant torsion of the Cartesian orthotropic homogeneous linearly elastic bar is considered. The cross-section of the prismatic bar is an isosceles right-angled triangular plane domain. An approximate analytical method is presented to obtain Prandtl’s stress function, shearing stresses, and torsional rigidity. Upper and lower bounds for the torsional rigidity are provided. The obtained results for shearing stresses are verified through FEM computation.